(Hot) Dogs: Of fast food and companion species. Issue 1 (9th August 2012) - Thomson, Claire
The encounter between dog and (potential) owner is the catalyst for Natan's interrogation of the human/animal binary. Drawing on Haraway's concept of 'companion species', the article explores the film's critique of a double commodification of animals: as pets, and in agribusiness, via Viggo's kebab-shop chain and consumption of meat.